10.2% Power Conversion Efficiency Polymer Tandem Solar Cells Consisting of Two Identical Sub‐Cells. (29th May 2013) - You, Jingbi; Chen, Chun‐Chao; Hong, Ziruo; Yoshimura, Ken; Ohya, Kenichiro; Xu, Run; Ye, Shenglin; Gao, Jing; Li, Gang; Yang, Yang
<x xml:space="preserve">Abstract</x> Polymer tandem solar cells with 10.2% power conversion efficiency are demonstrated via stacking two PDTP‐DFBT:PC71BM bulk heterojunctions, connected by MoO3/PEDOT:PSS/ZnO as an interconnecting layer. The tandem solar cells increase the power conversion efficiency of the PDTP‐DFBT:PC71BM system from 8.1% to 10.2%, successfully demonstrating polymer tandem solar cells with identical sub‐cells of double‐digit efficiency. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>